2013
DOI: 10.1111/cmi.12231
|View full text |Cite
|
Sign up to set email alerts
|

LOSoligosaccharide modification enhances dendritic cell responses to meningococcal native outer membrane vesicles expressing a non‐toxic lipidA

Abstract: SummaryOuter membrane vesicles (OMV) are released by many bacteria, and contain immunogenic antigens in addition to harmful inflammatory factors, like lipopolysaccharides. Chemically detoxified OMV have been used in vaccines against Neisseria meningitidis (Nm); however, little is known about their interaction with antigen presenting cells. In this study, we investigated the interaction of Nm OMV with human dendritic cells (DC) to gain further understanding of their biological activity. We engineered a novel se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
5
1
1
Order By: Relevance
“…Interestingly, production of the anti-inflammatory cytokine IL-10 by AMac was not significantly increased in comparison to live bacteria for any of the Nagasaki vesicles tested (liquid, plate or sonicate). This finding is in contrast to results previously seen by other researchers stimulating host dendritic cells with OMV isolated from Neisseria meningitidis , in which significant production of IL-10 was observed [ 68 ]. This may indicate that cell types are differentially effected by OMV (alveolar macrophages versus dendritic cells), that the observed level of stimulation is the maximum for the concentration of OMV used, or alternatively, that the live bacteria are somehow able to stimulate an IL-10 response [ 69 ], but OMV does not (lowering the immune response).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, production of the anti-inflammatory cytokine IL-10 by AMac was not significantly increased in comparison to live bacteria for any of the Nagasaki vesicles tested (liquid, plate or sonicate). This finding is in contrast to results previously seen by other researchers stimulating host dendritic cells with OMV isolated from Neisseria meningitidis , in which significant production of IL-10 was observed [ 68 ]. This may indicate that cell types are differentially effected by OMV (alveolar macrophages versus dendritic cells), that the observed level of stimulation is the maximum for the concentration of OMV used, or alternatively, that the live bacteria are somehow able to stimulate an IL-10 response [ 69 ], but OMV does not (lowering the immune response).…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that lgtB oligosaccharide truncation can significantly increase internalization of OMVs by human dendritic cells as compared with wild-type or galE truncated oligosaccharides (37). Moreover, the presence of lgtB truncated oligosaccharide in OMVs improved human DC maturation, IL-10, and interleukin-23 production by human DC and increased Th17 cell expansion (37).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, Shigella and Salmonella these enzymes are encoded by msbB (lpxM), htrB (lpxL) and pagP, which respectively add a myristoyl, lauroyl or palmitoyl group to the lipid A [51][52][53][54]. In Neisseria meningitidis, secondary acylation of lipid A is performed by lpxL1 and lpxL2 [55][56][57][58][59][60][61].…”
Section: Omv As Vaccinesmentioning
confidence: 99%